Terrorism, Media Coverage and Education: Evidence from Al-Shabaab Attacks in Kenya - Marco Alfano; Joseph-Simon Goerlach (Institute of Labor Economics (IZA), 2022)
We examine how terrorism alters the demand for education through perceived risks and returns by relating terrorist attacks to media signal coverage and schooling in Kenya. Exploiting geographical and temporal variation in wireless signal coverage and attacks, we establish that media access reinforces negative effects of terrorism on schooling. These effects are confirmed when we instrument both media signal and the incidence of attacks. For households with media access, we also find a significant relation between media content and schooling and a significant effect of attacks on self-reported fears and concerns. Based on these insights, we estimate a simple structural model where heterogeneous households experiencing terrorism form beliefs about risks and returns to education. We exploit the same quasi-experimental variation as in the reduced form analysis to identify how media change subjective expectations. The results show that households with media access significantly over-estimate fatality risks.
Keywords: D74; L82; F52; I21; 330; terrorism; media; expectations; education